Myoclonic status epilepticus induced by cefepime overdose requiring haemodialysis - Garin, Aude (BMJ Case Rep, 2019)
We report a case of cefepime neurotoxicity characterised by myoclonic status epilepticus with coma, in a context of acute renal failure and requiring one discontinuous conventional haemodialysis. Cefepime is a fourth-generation broad‐spectrum cephalosporin mainly used to treat hospital-acquired Gram-negative infections. Acute neurotoxicity is an increasingly reported adverse effect which occurs predominantly in patients with renal impairment. Renal replacement therapy has been proposed to treat this condition.